The effect of service quality in providing on customer satisfaction at Bank Syariah Indonesia Bandung - Tuti Sulastri; Tengku Ine Hendriana; Syagita Rachmawati (Enrichment : Journal of Management, 2025)
PT Bank Syariah Indonesia Tbk (BSI) is the result of a merger between PT Bank BRI Syariah Tbk, PT Bank Syariah Mandiri, and PT Bank BNI Syariah. It officially commenced operations on February 1, 2021. As a service provider, BSI is required to provide quality service to enhance customer satisfaction. This study aims to determine the effect of service quality through the provision of Hajj souvenirs on the satisfaction of Hajj savings customers at BSI KCP Bandung Kopo. The method used was quantitative with a saturated sample of 43 respondents, and data analysis was performed using SPSS version 26. The results indicate that the provision of Hajj souvenirs significantly influences customer satisfaction, with a calculated t-value of 4.750 > t-table 2.019. The coefficient of determination of 35.5% indicates that this factor contributes significantly to customer satisfaction, while 64.5% is influenced by other factors outside this study. Practically, these findings suggest that BSI can leverage the provision of relevant and meaningful souvenirs as part of its service differentiation strategy to strengthen customer loyalty, improve overall service experience, and gain a competitive advantage in the Islamic banking industry.